New Challenges for Sustainable Rural Development in the 21st Century (part 3) - Lorber, Lučka (Journal for Geography, 2010)
The concept of rural development has undergone an important transformation process during the last decades, which has gone hand-in-hand with changes in the countryside and new demands from society. Rapid changes in the international economy-globalisation, improved communications and reduced transportation costs, changing trade patterns for commodities, as well as emergence of important non-farm activities in rural regions – confront rural regions with some obvious threats, but also with significant opportunities. Against this background, policy makers increasingly recognise that traditional sectoral policies need to be upgraded and, in some cases, phased out and substituted with more appropriate instruments. Particular concerns are raised by the modest positive impact that agricultural subsidies have on general economic performance even in the most farming dependent communities. Indeed, with farm families relying increasingly on off-farm employment, the economic success of rural communities will depend on the development of new economic engines.
Keywords: sustainable rural development; rural transformations; rural communities